Upcycling of Polyethylene Wastes to Valuable Chemicals over Group VIII Metal‐decorated WO3 Nanosheets - Qimin Zhou; Weiqiang Gao; Deliang Wang; Yinlong Chang; Hanxi Guan; Khak Ho Lim; Xuan Yang; Pingwei Liu; Wen‐Jun Wang; Bo‐Geng Li; Qingyue Wang (Advanced Science)
Abstract Catalytic cracking of polyolefin wastes into valuable chemicals at mild conditions using non‐noble metal catalysts is highly attractive yet challenging. Herein it is reported that 2D tungsten trioxide (2D WO3) nanosheets, after decorating with group VIII metal promoters (i.e., Fe, Co, or Ni), convert high‐density polyethylene (HDPE) into alkylaromatics and olefins at low temperature and ambient pressure without using any solvent or hydrogen: 2D Ni/WO3 with abundant Brønsted acidic sites initiates HDPE cracking at a low temperature of 240 °C; 2D Fe/WO3 with low energy barrier of cyclization achieves a high HDPE conversion to 84.2% liquid hydrocarbons with a selectivity of 30.9% to aromatics at 300 °C. In‐situ spectroscopic investigations and supplementary theoretical calculations illustrate that these aromatics are formed through the cyclization of alkene intermediates. These 2D catalysts also display high efficiency in the low‐temperature cracking of single‐use commercial polyethylene wastes such as packaging bags and bottles. This work has demonstrated the high potential of 2D non‐noble metal catalysts in the efficient upcycling of waste polyolefin at mild conditions.